Monte Carlo-based scatter correction considering the tailing effect of a CdTe detector for dual-isotope brain SPECT imaging. (29th July 2016) - Suzuki, Atsuro; Takeuchi, Wataru; Ueno, Yuichiro; Kobashi, Keiji; Toyonaga, Takuya; Shiga, Tohru; Tamaki, Nagara
Abstract: A Monte Carlo (MC)-based scatter correction method considering the tailing effect of a CdTe detector was developed for dual-isotope brain single-photon emission computed tomography (SPECT) imaging using technetium-99m ( 99m Tc) and iodine-123 ( 123 I), and its accuracy was validated by measuring phantoms. The tailing effect was modeled by convolutions of energy spectra obtained by geometry and tracking (GEANT) simulation with energy smoothing kernels. In our experimental phantom studies, quantitative accuracy and image contrast in the reconstructed image of dual-isotope-filled phantoms with our MC-based scatter correction method (Dual_SC) were compared with those of single-isotope-filled phantoms (Single_SC). The quantitative accuracy was evaluated by the percent error between the estimated activity concentration and true activity concentration. In our six-compartment phantom study with six different activity concentrations, the mean absolute percent errors of 99m Tc for Single_SC and Dual_SC were 1.7% and 2.8%, respectively, while those of 123 I for Single_SC and Dual_SC were 4.8% and 5.6%, respectively. In our striatal phantom study, the percent errors in the background regions for Single_SC and Dual_SC were less than 2% for both 99m Tc and 123 I. The image contrast was evaluated by the percent contrast of a cold or hot spot region to a background region. In our cold rod phantom study, the mean percent contrasts in the cold rod regions of 99m Tc for Single_SC and Dual_SC were 66.2% and 65.0%, respectively, while those of 123 I for Single_SC and Dual_SC were 59.3% and 61.6%, respectively. In our striatal phantom study, the percent contrasts in the striatal regions of 99m Tc for Single_SC and Dual_SC were 56.1% and 56.1%, respectively, while those of 123 I for Single_SC and Dual_SC were 39.8% and 40.0%, respectively. In conclusion, dual-isotope imaging with the CdTe-based brain SPECT system and our MC-based scatter correction method can provide comparable quantitative accuracy and image contrast to those of single-isotope imaging.